Edycja cyfrowa „Aratusa” i „Fenomenów” Jana Kochanowskiego – problematyka aparatu naukowego - Hojdis, Bogdan (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
In this text, the author uses the critical edition of Jan Kochanowski’s Aratus and Fenomena being prepared at the Institute of Literary Research of the Polish Academy of Sciences to present the practical aspects of creating a functional back matter in relation to the first digital proof of such an edition. The rules for publishing Old Polish texts, which were created at the Institute in the late 1950s are confronted with the practice of classical philologists (in this case, Neo-Latinists) and with the contemporary digital toolset used for both textological research and publishing. It turns out that the adaptation of an analog edition to a digital one might cause a change in the concept of a given edition and that in such cases a significant role is played by the programmers working with the scientific editors and the editorial team.